Frontier Computing Theory, Technologies and Applications (FC 2017) - Hung, Jason C.; Yen, Neil Y.; Hui, Lin (Lecture Notes in Electrical Engineering, 2018)
This book gathers the proceedings of the 6th International Conference on Frontier Computing, held in Osaka, Japan on July 12-14, 2017, and provides comprehensive coverage of the latest advances and trends in information technology, science and engineering. It addresses a number of broad themes, including communication networks, business intelligence and knowledge management, web intelligence, and related fields that inspire the development of information technology. The respective contributions cover a wide range of topics: database and data mining, networking and communications, web and internet of things, embedded systems, soft computing, social network analysis, security and privacy, optical communication, and ubiquitous/pervasive computing. Many of the papers outline promising future research directions, and the book will benefit students, researchers and professionals alike. Further, it offers a useful reference guide for newcomers to the field.